Guiding the Behavior of Young Women in Family Planning and Prevention of Anemia through Peer Group Empowerment as an Effort to Prevent Stunting - Manaf, Nawawi (Journal of Health Science and Medical Therapy, 2023)
The problems of young women are anemia, child marriage and reproductive health. The prevalence of anemia in young women in Indonesia increased from 26.4 % to 48.9%. It is necessary to form a peer group to become a peer companion which aims to increase knowledge, attitudes and actions regarding family planning, age delay marriage, reproductive health and prevention of anemia by applying booklet media and Fe Tablet consumption monitoring cards. The target audience is 50 young women in SMP 9 Bengkulu City and 50 young women in Kupang City. Assistance is carried out for 4 months (August-November 2020) using the small group method. There was an increase in the knowledge score of 13.98 points (p=0.0001) before and after the mentoring activities. Increased knowledge scores in Bengkulu City (12.11 points) and in Kupang City (15.32 points). There was a significant increase in attitude scores of 0.73 points (p=0.0001). Before and after mentoring activities in Bengkulu City (0.67 points) and in Kupang City (0.40 points) and young women became obedient in consuming Fe tablets. The school, in collaboration with health workers, needs to continue to empower Peer Groups to provide assistance with small group methods to improve adolescent health, prevent anemia, and prevent giving birth to stunted children in the future.